The Node Weight Dependent Traveling Salesperson Problem: Approximation Algorithms and Randomized Search Heuristics - Bossek, Jakob; Casel, Katrin; Kerschke, Pascal; Neumann, Frank (Proceedings of the Genetic and Evolutionary Computation Conference)
Several important optimization problems in the area of vehicle routing can be seen as variants of the classical Traveling Salesperson Problem (TSP). In the area of evolutionary computation, the Traveling Thief Problem (TTP) has gained increasing interest over the last 5 years. In this paper, we investigate the effect of weights on such problems, in the sense that the cost of traveling increases with respect to the weights of nodes already visited during a tour. This provides abstractions of important TSP variants such as the Traveling Thief Problem and time dependent TSP variants, and allows to study precisely the increase in difficulty caused by weight dependence. We provide a 3.59-approximation for this weight dependent version of TSP with metric distances and bounded positive weights. Furthermore, we conduct experimental investigations for simple randomized local search with classical mutation operators and two variants of the state-of-the-art evolutionary algorithm EAX adapted to the weighted TSP. Our results show the impact of the node weights on the position of the nodes in the resulting tour.
Keywords: dynamic optimization; evolutionary algorithms; running time analysis; theory

Dynamic Bi-Objective Routing of Multiple Vehicles - Bossek, Jakob; Grimme, Christian; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference)
In practice, e.g. in delivery and service scenarios, Vehicle-Routing-Problems (VRPs) often imply repeated decision making on dynamic customer requests. As in classical VRPs, tours have to be planned short while the number of serviced customers has to be maximized at the same time resulting in a multi-objective problem. Beyond that, however, dynamic requests lead to the need for re-planning of not yet realized tour parts, while already realized tour parts are irreversible. In this paper we study this type of bi-objective dynamic VRP including sequential decision making and concurrent realization of decisions. We adopt a recently proposed Dynamic Evolutionary Multi-Objective Algorithm (DEMOA) for a related VRP problem and extend it to the more realistic (here considered) scenario of multiple vehicles. We empirically show that our DEMOA is competitive with a multi-vehicle offline and clairvoyant variant of the proposed DEMOA as well as with the dynamic single-vehicle approach proposed earlier.
Keywords: decision making; dynamic optimization; evolutionary algorithms; multi-objective optimization; vehicle routing

Anytime Behavior of Inexact TSP Solvers and Perspectives for Automated Algorithm Selection - Bossek, Jakob; Kerschke, Pascal; Trautmann, Heike (2020 IEEE Congress on Evolutionary Computation (CEC))
The Traveling-Salesperson-Problem (TSP) is arguably one of the best-known NP-hard combinatorial optimization problems. The two sophisticated heuristic solvers LKH and EAX and respective (restart) variants manage to calculate close-to optimal or even optimal solutions, also for large instances with several thousand nodes in reasonable time. In this work we extend existing benchmarking studies by addressing anytime behaviour of inexact TSP solvers based on empirical runtime distributions leading to an increased understanding of solver behaviour and the respective relation to problem hardness. It turns out that performance ranking of solvers is highly dependent on the focused approximation quality. Insights on intersection points of performances offer huge potential for the construction of hybridized solvers depending on instance features. Moreover, instance features tailored to anytime performance and corresponding performance indicators will highly improve automated algorithm selection models by including comprehensive information on solver quality.

Initial Design Strategies and Their Effects on Sequential Model-Based Optimization: An Exploratory Case Study Based on BBOB - Bossek, Jakob; Doerr, Carola; Kerschke, Pascal (Proceedings of the Genetic and Evolutionary Computation Conference)
Sequential model-based optimization (SMBO) approaches are algorithms for solving problems that require computationally or otherwise expensive function evaluations. The key design principle of SMBO is a substitution of the true objective function by a surrogate, which is used to propose the point(s) to be evaluated next. SMBO algorithms are intrinsically modular, leaving the user with many important design choices. Significant research efforts go into understanding which settings perform best for which type of problems. Most works, however, focus on the choice of the model, the acquisition function, and the strategy used to optimize the latter. The choice of the initial sampling strategy, however, receives much less attention. Not surprisingly, quite diverging recommendations can be found in the literature. We analyze in this work how the size and the distribution of the initial sample influences the overall quality of the efficient global optimization (EGO) algorithm, a well-known SMBO approach. While, overall, small initial budgets using Halton sampling seem preferable, we also observe that the performance landscape is rather unstructured. We furthermore identify several situations in which EGO performs unfavorably against random sampling. Both observations indicate that an adaptive SMBO design could be beneficial, making SMBO an interesting test-bed for automated algorithm design.
Keywords: continuous black-box optimization; design of experiments; initial design; sequential model-based optimization

Optimising Tours for the Weighted Traveling Salesperson Problem and the Traveling Thief Problem: A Structural Comparison of Solutions - Bossek, Jakob; Neumann, Aneta; Neumann, Frank (Parallel Problem Solving from Nature (PPSN XVI))
The Traveling Salesperson Problem (TSP) is one of the best-known combinatorial optimisation problems. However, many real-world problems are composed of several interacting components. The Traveling Thief Problem (TTP) addresses such interactions by combining two combinatorial optimisation problems, namely the TSP and the Knapsack Problem (KP). Recently, a new problem called the node weight dependent Traveling Salesperson Problem (W-TSP) has been introduced where nodes have weights that influence the cost of the tour. In this paper, we compare W-TSP and TTP. We investigate the structure of the optimised tours for W-TSP and TTP and the impact of using each others fitness function. Our experimental results suggest (1) that the W-TSP often can be solved better using the TTP fitness function and (2) final W-TSP and TTP solutions show different distributions when compared with optimal TSP or weighted greedy solutions.
Keywords: Evolutionary algorithms; Node weight dependent TSP; Traveling Thief Problem

Towards Decision Support in Dynamic Bi-Objective Vehicle Routing - Bossek, Jakob; Grimme, Christian; Rudolph, Günter; Trautmann, Heike (2020 IEEE Congress on Evolutionary Computation (CEC))
We consider a dynamic bi-objective vehicle routing problem, where a subset of customers ask for service over time. Therein, the distance traveled by a single vehicle and the number of unserved dynamic requests is minimized by a dynamic evolutionary multi-objective algorithm (DEMOA), which operates on discrete time windows (eras). A decision is made at each era by a decision-maker, thus any decision depends on irreversible decisions made in foregoing eras. To understand effects of sequences of decision-making and interactions/dependencies between decisions made, we conduct a series of experiments. More precisely, we fix a set of decision-maker preferences D and the number of eras n{$<$}inf{$>$}t{$<$}/inf{$>$} and analyze all $|D|\^{n_t}$ combinations of decision-maker options. We find that for random uniform instances (a) the final selected solutions mainly depend on the final decision and not on the decision history, (b) solutions are quite robust with respect to the number of unvisited dynamic customers, and (c) solutions of the dynamic approach can even dominate solutions obtained by a clairvoyant EMOA. In contrast, for instances with clustered customers, we observe a strong dependency on decision-making history as well as more variance in solution diversity.

Evolving Diverse Sets of Tours for the Travelling Salesperson Problem - Do, Anh Viet; Bossek, Jakob; Neumann, Aneta; Neumann, Frank (Proceedings of the Genetic and Evolutionary Computation Conference)
Evolving diverse sets of high quality solutions has gained increasing interest in the evolutionary computation literature in recent years. With this paper, we contribute to this area of research by examining evolutionary diversity optimisation approaches for the classical Traveling Salesperson Problem (TSP). We study the impact of using different diversity measures for a given set of tours and the ability of evolutionary algorithms to obtain a diverse set of high quality solutions when adopting these measures. Our studies show that a large variety of diverse high quality tours can be achieved by using our approaches. Furthermore, we compare our approaches in terms of theoretical properties and the final set of tours obtained by the evolutionary diversity optimisation algorithm.
Keywords: diversity maximisation; evolutionary algorithms; travelling salesperson problem

Runtime Analysis of Evolutionary Algorithms with Biased Mutation for the Multi-Objective Minimum Spanning Tree Problem - Roostapour, Vahid; Bossek, Jakob; Neumann, Frank (Proceedings of the 2020 Genetic and Evolutionary Computation Conference)
Evolutionary algorithms (EAs) are general-purpose problem solvers that usually perform an unbiased search. This is reasonable and desirable in a black-box scenario. For combinatorial optimization problems, often more knowledge about the structure of optimal solutions is given, which can be leveraged by means of biased search operators. We consider the Minimum Spanning Tree (MST) problem in a single- and multi-objective version, and introduce a biased mutation, which puts more emphasis on the selection of edges of low rank in terms of low domination number. We present example graphs where the biased mutation can significantly speed up the expected runtime until (Pareto-)optimal solutions are found. On the other hand, we demonstrate that bias can lead to exponential runtime if "heavy" edges are necessarily part of an optimal solution. However, on general graphs in the single-objective setting, we show that a combined mutation operator which decides for unbiased or biased edge selection in each step with equal probability exhibits a polynomial upper bound - as unbiased mutation - in the worst case and benefits from bias if the circumstances are favorable.
Keywords: biased mutation; evolutionary algorithms; minimum spanning tree problem; runtime analysis

Deep Learning as a Competitive Feature-Free Approach for Automated Algorithm Selection on the Traveling Salesperson Problem - Seiler, Moritz; Pohl, Janina; Bossek, Jakob; Kerschke, Pascal; Trautmann, Heike (Parallel Problem Solving from Nature (PPSN XVI))
In this work we focus on the well-known Euclidean Traveling Salesperson Problem (TSP) and two highly competitive inexact heuristic TSP solvers, EAX and LKH, in the context of per-instance algorithm selection (AS). We evolve instances with nodes where the solvers show strongly different performance profiles. These instances serve as a basis for an exploratory study on the identification of well-discriminating problem characteristics (features). Our results in a nutshell: we show that even though (1) promising features exist, (2) these are in line with previous results from the literature, and (3) models trained with these features are more accurate than models adopting sophisticated feature selection methods, the advantage is not close to the virtual best solver in terms of penalized average runtime and so is the performance gain over the single best solver. However, we show that a feature-free deep neural network based approach solely based on visual representation of the instances already matches classical AS model results and thus shows huge potential for future studies.
Keywords: Automated algorithm selection; Deep learning; Feature-based approaches; Traveling Salesperson Problem

A Multi-Objective Perspective on Performance Assessment and Automated Selection of Single-Objective Optimization Algorithms - Bossek, Jakob; Kerschke, Pascal; Trautmann, Heike (Applied Soft Computing)
We build upon a recently proposed multi-objective view onto performance measurement of single-objective stochastic solvers. The trade-off between the fraction of failed runs and the mean runtime of successful runs – both to be minimized – is directly analyzed based on a study on algorithm selection of inexact state-of-the-art solvers for the famous Traveling Salesperson Problem (TSP). Moreover, we adopt the hypervolume indicator (HV) commonly used in multi-objective optimization for simultaneously assessing both conflicting objectives and investigate relations to commonly used performance indicators, both theoretically and empirically. Next to Penalized Average Runtime (PAR) and Penalized Quantile Runtime (PQR), the HV measure is used as a core concept within the construction of per-instance algorithm selection models offering interesting insights into complementary behavior of inexact TSP solvers. \textbullet The multi-objective perspective is naturally generalizable to multiple objectives. \textbullet Proof of relationship between HV and the PAR in the considered bi-objective space. \textbullet New insights into complementary behavior of stochastic optimization algorithms.
Keywords: Algorithm selection; Combinatorial optimization; Multi-objective optimization; Performance measurement; Traveling Salesperson Problem

Benchmarking in Optimization: Best Practice and Open Issues - Bartz-Beielstein, Thomas; Doerr, Carola; van den Berg, Daan; Bossek, Jakob; Chandrasekaran, Sowmya; Eftimov, Tome; Fischbach, Andreas; Kerschke, Pascal; Cava, William La; Lopez-Ibanez, Manuel; Malan, Katherine M.; Moore, Jason H.; et al. (Corr)

Geschichte(n) der deutschen Migrationsgesellschaft. Jugendliche erzählen begründete historische Geschichten Eine Unterrichtsreihe für das Portal Zwischentöne.info - Fastlabend-Vargas, Daniel

Erinnerung und Identität: Literarische Konstruktionen in Doeschka Meijsings Prosa - Lammer, Christina

"Die Bombardierung von Brüssel - teil 1" (PODCAST) - Huybrechts, Yves

Den Kaiser erpressen. Der Fall Jever zwischen Burgundischem Reichskreis und Reichskammergericht, 1737-1739 - Huybrechts, Yves (Historisches Jahrbuch)

"Ein Gespräch mit Guy Vanhengel - Ein Gespräch mit dem Vizepräsidenten des Brüsseler Parlaments, in zwei Teilen." (VIDEO) - Huybrechts, Yves

Interview zur Ausstellung "Rubens und der Barock im Norden" - 2 Teile (VIDEO) - Huybrechts, Yves

Ironie als forcierte Form. Hans Magnus Enzensbergers Versepos Der Untergang der Titanic - Diedrich, Alena (Forcierte Form: Deutschsprachige Versepik des 20. und 21. Jahrhunderts im europäischen Kontext)

Lyrik im Vormärz - Diedrich, Alena (Handbuch Vormärz)

Nikolaus Lenau - Diedrich, Alena (Handbuch Vormärz)

Medienpädagogik und Hochschuldidaktik - Neiske, Iris; Bücker, Diana (Medienpädagogik als Schlüsseldisziplin in einer mediatisierten Welt. Perspektiven aus Theorie, Empirie und Praxis 37)

Impulse 5. Texte und Bilder zur Kunstvermittlung: Go West! Kunst- und Ausstellungsszene New York 2019.

"Was machst du gerade?" Essays aus dem Atelier in Zeiten von Corona

Festrede auf Maria v. Welser anlässlich der Verleihung der Ehrendoktorwürde am 14.11.2019 durch die kulturwissenschaftliche Fakultät der Universität Paderborn - Autsch, Sabiene (PUR [= Paderborner Universitätsreden. Hg. von. Prof. em. Dr. Dr. hc. malt. Peter Freese])

Profession und Disziplin. Ein Schreibgespräch über den Weg durch die Fächer, Schreibdidaktik als Feldforschung (und - nebenbei - die Rettung der Schriftkultur). - Karsten, Andrea; Weisberg, Jan (JoSch - Journal der Schreibwissenschaft)

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 8.2: Synopse der Manuskriptbände V bis X, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2019 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1445.01036)

Alice im Wunderland. Ein Klassiker der Kinderliteratur als Künstlerbuch - Pauls, Karina (Kunst+Unterricht 441/442)

Soziale Investition - Dahmen, Stephan; Bonvin, Jean-Michel (Wörterbuch der Schweizer Sozialpolitik)

Die Entstehung von Sternen und Planeten - Stricker, Ina; Müller, Lenka; Hohmann, Sascha (Astronomie + Raumfahrt im Unterricht)

Die Astronomie der Inka. Teil 3 – Der Himmel über Cusco - Hohmann, Sascha (Astronomie + Raumfahrt im Unterricht)

Die Astronomie der Inka. Teil 1 - Weltbild, Religion und Kalender - Hohmann, Sascha (Astronomie + Raumfahrt im Unterricht)

Die Astronomie der Inka. Teil 2 - Machu Picchu - Hohmann, Sascha (Astronomie + Raumfahrt im Unterricht)

Calculating the distributions of number, mass and luminosity of the stars with the help of MS Excel - Hohmann, Sascha (European Journal of Physics)
Abstract Astrophysical topics can be treated with the methods of different areas of physics, mathematics and other natural sciences. The integration of these topics into such areas could improve students’ motivation and strengthen the connections between different fields of the mentioned sciences. In this article, an example of the connection between the physics of the stars and that of their statistical distributions is given. The usage of Microsoft Excel simplifies the mathematical requirements and gives the possibility of seeing the changes of distribution with the growing age of the regarded population of stars. The changes are a direct consequence to the limited lifetime of the stars and the limited age of the considered population of stars.
Keywords: General Physics and Astronomy

Die weiße Frau als Kulturträgerin? Postkoloniale Perspektiven auf Geschlecht am Beispiel von Wolfgang Koeppens Tauben im Gras - Kißling, Magdalena (Der Deutschunterricht)

Adipöse Personen im Feuerwehreinsatz - Wolff, Jens
Einsätze mit adipösen Personen stellen die Feuerwehr und den Rettungsdienst vor vielfältige Herausforderungen, da Rettung und Transport für die Einsatzkräfte eine logistische Hürde mit Mehraufwand und Risiken darstellen. Der Autor untersucht die Besonderheiten bei bestimmten Einsatzszenarien; angefangen bei der Trageunterstützung für den Rettungsdienst über den Verkehrsunfall mit eingeklemmter adipöser Person bis hin zum Brandeinsatz mit schwergewichtigen Menschen. Mögliche Einsätze werden abgegrenzt und etwaige Besonderheiten im Vergleich zu den üblichen "Standardeinsätzen" diskutiert. Einblicke in rettungsdienstliche Aspekte bei Einsätzen mit adipösen Patientinnen und Patienten vervollständigen das Buch.

Aushandlungsprozesse über Freiheiten und Grenzen im selbstregulierten Lernen. Erwartungen und Handlungsmuster bei Schüler*innen und Lehrpersonen im Übergangssystem - Daniel-Söltenfuß, Desiree (bwp@)

Video analysis in Design-Based Research – Findings of a project on self-organised learning at a vocational school - Gössling, Bernd; Daniel, Desiree (EDeR. Educational Design Research)
The use of video analysis in Design-Based Research (DBR) seems to be promising, because the quality of video data matches the reality of educational fields. Educational fields are multidimensional and complex. And more than other types of data, video may capture, for example, the simultaneity of verbal and non-verbal interactions. This seems to be valuable in the quest for new insights and better designs of educational interventions. However, to date there has been limited use of video data in researching their design. This paper aims at reflecting how the benefits of video-based analysis may be utilised in DBR. Experiences with the collection and analysis of video data in a project to design self-organised learning (SOL) at a vocational school in Germany will be used as a case study to illustrate the type of findings that may feed into the DBR process. In this case, the project school had already introduced a sophisticated SOL model but was experiencing various implementation difficulties. Resolving issues like this requires insights into how exactly a concept is realised and what happens in the field. Therefore, video data on classroom interactions was gathered and sub-sequently analysed using the documentary method. This led to the reconstruction of two different types of orientation that were guiding the students when they dealt with their self-organised learning environment. In a subversive orientation, students playfully infiltrate the formal learning space with peer activities. In a confirming orientation, students stick to both, the (informal) rules of the (formal) learning arrangement and of the peer environment, thus expressing respect for the boundary between these two worlds. These findings have been used to redesign the SOL intervention.
Keywords: Pulmonary and Respiratory Medicine; Pediatrics; Perinatology and Child Health

"Durch Manhattan." Stadt als Bewegungsraum - Autsch, Sabiene (Urbane Kulturen und Räume intermedial)

Ästhetische Forschung des Urbanen - Autsch, Sabiene (Impulse 5. Texte und Bilder zur Kunstvermittlung: Go West! Kunst- und Ausstellungsszene New York 2019)

"Go West." Sich in Bewegung setzen - Autsch, Sabiene (Impulse 5. Texte und Bilder zur Kunstvermittlung: Go West! Kunst- und Ausstellungsszene New York 2019)

Erfolgsfaktoren digitaler Transformationsprozesse in KMU - Heitmann, Ingmar (Neuere Entwicklungen in Produktionn und Controlling)

Varianten- und Komplexitätsmanagement im produzierenden Gewerbe - Puls, Christoph (Neuere Entwicklungen in Produktionn und Controlling)

Digitalisierung des Produktionscontrollings in KMU - Koch, Christian (Neuere Entwicklungen in Produktionn und Controlling)

Kapazitätsplanung unter besonderer Berücksichtigung produktionsseitiger Risiken - Opitz, Oliver (Neuere Entwicklungen in Produktion und Controlling)

Brückenschläge zwischen Musikwissenschaft und Informatik. Theoretische und praktische Aspekte der Kooperation

Don't patronize me! An experiment on preferences for authorship - Lübbecke, Silvia; Schnedler, Wendelin (Journal of Economics & Management Strategy)

Hardening Soft Information: A Transformer-Based Approach to Forecasting Stock Return Volatility - Caron, Matthew; Müller, Oliver (2020 IEEE International Conference on Big Data (Big Data))
Historically, the field of financial forecasting almost exclusively relied on so-called hard information – i.e., numerical data with well-defined and unambiguous meaning. Over the last few decades, however, researchers and practitioners alike have, following the advances in natural language understanding, started recognizing the benefits of integrating soft information into financial modelling. In line with the above, this paper examines whether contemporary attention-based sequence-to-sequence models, known as Transformers, can help improve stock return volatility prediction when applied to corporate annual reports. Using a publicly available benchmark dataset, we show, in an empirical analysis, that out-of-the-box Transformer models have the ability to outmatch current state-of-the-art results and, more importantly, that our proposed feature-based Transformer approach can outperform a robust numerical baseline. To the best of our knowledge, this is the first empirical study focusing on stock return volatility prediction (1) to ever experiment with state-of-the-art Transformer architectures and (2) to demonstrate that a model based solely on soft information can surpass its numerical counterpart. Furthermore, we show that by including an additional numerical feature into our best text-only model, we can push the performance of our model even further, suggesting that soft and hard information contain different predictive signals.

Data Privacy in Retail - Martin, K. D.; Kim, J. J.; Palmatier, R. W.; Steinhoff, Lena; Stewart, D. W.; Walker, B. A.; Wang, Y.; Weaven, S. K. (Journal of Retailing)

Toward a Comprehensive Framework of Value Proposition Development: From Strategy to Implementation - Payne, A.; Steinhoff, Lena; Frow, P.; Eggert, A. (Industrial Marketing Management)

Understanding and Managing Customer Value Propositions: Introduction to the Special Issue - Eggert, A.; Frow, P.; Payne, A.; Steinhoff, Lena (Industrial Marketing Management)

Adolescents’ engagement at school vs. leisure time and their emotional involvement. - Knickenberg, Margarita; Zurbriggen, Carmen; Venetz, Martin

Social relationships in students with special educational needs. - Knickenberg, Margarita

Individualisierung des Lernens im inklusiven Unterricht aus der Perspektive von Lehrkräften und Kindern. - Knickenberg, Margarita

Das emotionale Erleben von Jugendlichen in Abhängigkeit ihres Engagements in Schule und Freizeit. - Knickenberg, Margarita; Zurbriggen, Carmen; Venetz, Martin

Students’ emotional experience during peer interactions in different academic tracks. - Knickenberg, Margarita; Zurbriggen, Carmen

Rezension zu: Peltzer, Jörg: Fürst werden. Rangerhöhungen im 14. Jahrhundert. Das römisch-deutsche Reich und England im Vergleich. Berlin-Boston 2019. ISBN 978-3-11-063902-5 - Bröker, Christina (HsozKult)

PQ³. Paderborner Qualitätsstern zur Einschätzung der Kooperation im Übergang Kita - Grundschule - Büker, Petra; Höke, Julia;; Ogrodowski, Jana; Vollmann, Britta
Paderborn: Universität Paderborn Online-Ressource: upb.de/paderborner-qualitaetsstern-kita-gs bzw. https://blogs.uni-paderborn.de/paderborner-qualitaetsstern/ bzw. https://blogs.uni-paderborn.de/paderborner-qualitaetsstern/zum-instrument/

Kooperatives Arbeiten von Studierenden des Lehramts an Grund- und Förderschulen als Vorbereitung auf den inklusiven Unterricht in der Grundschule - Schulze, Jan Roland; Hoya, Fabian Karl; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank (Sonderpädagogik und Bildungsforschung – Fremde Schwestern?)

Total Digital? - Mind on the net? Geist im Netz? L’ esprit dans le réseau?. Reihe Forum Philosophie International. (Stefan Düfel: Lehrerbibliothek: Rezension)

Lesestrategien, Zeitschrift für Didaktik der Philosophie und Ethik

Handbuch Medien im Philosophie- und Ethikunterricht

Kants kategorischer Imperativ im sprachsensiblen Philosophieunterricht. Sapere Aude – Habe Mut, dich Primärquellen zu bedienen. (gekürzt) - Albus, Vanessa; Jost, Leif Marvin (Ethik & Unterricht)

Thesen zur Konstituierung einer interdisziplinären Metapherndidaktik - Albus, Vanessa (Metaphernforschung in interdisziplinäreren und interdiskursiven Perspektiven)

Digitalisierung und Sprachförderung als Triebfeder der Drittmittel- und Preismaschinerie. Ein kritischer Kommentar - Albus, Vanessa (Total Digital? - Mind on the net? Geist im Netz? L’ esprit dans le réseau?)

Philosophie und Ethik in der Lehrerinnen und Lehrerbildung - Albus, Vanessa (Handbuch Lehrerinnen- und Lehrerbildung)

Der Stachel der Melancholie. Philosophische Bildung in pandemischen Zeiten - Albus, Vanessa (Bildung und Erziehung im Ausnahmezustand. Philosophische Reflexionsangebote zur COVID-19-Pandemie)

Caroline Heinrich, Christian Thein: „Das philosophiedidaktische Dreieck in der Diskussion - Albus, Vanessa; Burkard, Anne (Information Philosophie)

Medien im Ethik- und Philosophieunterricht - Albus, Vanessa (Handbuch Medien im Philosophie- und Ethikunterricht)

Texte – Lesen und Verstehen - Albus, Vanessa (Handbuch Medien im Philosophie- und Ethikunterricht)

Lesen im Philosophie- und Ethikunterricht - Albus, Vanessa (ZDPE)

Im Interview mit…. - Albus, Vanessa; Petermann, Hans-Bernhard (ZDPE)

Kristina Peuschel, Anne Burkard (Hrsg.): Sprachliche Bildung und DaZ in den geistes- und gesellschaftlichen Fächern. Tübingen: narr Studienbücher 2019. 259 S. - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Büşra Çakıl: Die Rehabilitierung des Ehrbegriffs. Baden-Baden: Tectum 2018. 210 S. - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Christine Garbe: Lesekompetenz fördern. Stuttgart: Reclam 2020.129 S. - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

A Runtime System for Finite Element Methods in a Partitioned Global Address Space - Groth, Stefan; Grünewald, Daniel; Teich, Jürgen; Hannig, Frank (Proceedings of the 17th ACM International Conference on Computing Frontiers (CF '2020))

“Dear Stranger, This Looks Good on You”: The Effect of Ambiguous Interactive Virtual Presence on Store Loyalty in Offline Retailing - Reimer, T.; Steinhoff, Lena; Leyer, M. (2020 Winter AMA Conference Proceedings, San Diego)

Self-Esteem and Social Esteem. Normative Issues. (Human Affairs)

“D’Holbach on (Dis-)Esteeming Talent.” - Blank, Andreas (Journal of Modern Philosophy)

“Presumptions and Cognitive Simplicity in Leibniz and Early Modern Legal Theory.” - Blank, Andreas (Rechts- und Staatsphilosophie bei G. W. Leibniz.)

Review of Marine Picon, Normes et objets du savoir dans les premiers essais leibnitiens - Blank, Andreas (Studia Leibnitiana)

Kant, Linnaeus, and the economy of nature - Wells, Aaron (Studies in History and Philosophy of Science Part C: Studies in History and Philosophy of Biological and Biomedical Sciences)
Keywords: History and Philosophy of Science; History; General Medicine

L’imagination chez Descartes et ses contemporains (Les Cahiers Philosophiques de Strasbourg)

L'anatomie de la mélancolie chez Michel de Montaigne et Félix Platter - Muller, Jil (Montaigne Studies An Interdisciplinary Forum)

Montaigne et Descartes: L’imagination dans les passions - Muller, Jil (L’imagination chez Descartes et ses contemporains)

Présentation - Muller, Jil (L'imagination chez Descartes et ses contemporains)

Maria Magdalena: die Erstzeugin des Auferstandenen als „große Sünderin“? Diffamierende Umdeutungen der Apostelin - Taschl-Erber, Andrea (Bibel falsch verstanden. Hartnäckige Fehldeutungen biblischer Texte erklärt)

¿Mujeres des diáconos o diáconos mujer? - Taschl-Erber, Andrea (San Pablo y las mujeres (Las palabras y los dias))

Steuerliche Entlastungsmöglichkeiten für kleine und mittlere Unternehmen wegen der COVID-19-Pandemie - Giese, Henning; Graßl, Benjamin; Holtmann, Svea; Krug, Philipp (Deutsches Steuerrecht)

An Approach for Data Pipeline with Distributed Query Engine for Industrial Applications - Ghosh Chowdhury, Arnab; Illian, Marvin; Wisniewski, Lukasz; Jasperneite, Jurgen (2020 25th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))

A Process to Develop Lean Big-Data Platform Architectures for Industrial Manufacturing Contexts - Illian, Marvin; Althoff, Simon; Karl, Holger (2020 25th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))

“Leibniz: sobre las presunciones y la simplicidad cognitiva” - Blank, Andreas (Tópicos. Revista de filosofía de la Universidad de Santa Fe)

Die Nutzung digitaler Medien aus der Perspektive der Lehrkräfte - Drossel, Kerstin; Eickelmann, Birgit; Niemann, Jan; Vennemann, Mario (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Sichtweisen von Lehrkräften zum Lernen und Lehren mit digitalen Medien - Niemann, Jan; Eickelmann, Birgit; Drossel, Kerstin (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Lehrerausbildung zum Lernen und Lehren mit digitalen Medien - Drossel, Kerstin; Eickelmann, Birgit; Labusch, Amelie; Niemann, Jan (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

“Helvétius’s Challenge: Moral Luck, Political Constitutions and the Economy of Esteem.” - Blank, Andreas (European Journal of Philosophy)

Unverfügbares Verinnerlichen. Figuren der Einverleibung zwischen Eucharistie und Anthropophagie - Al-Taie, Yvonne; Famula, Marta (Amsterdamer Beiträge zur neueren Germanistik)

Das große Welttheater. Eine überzeitliche Chiffre des Barock /Pedro Calderón de la Barca – El gran teatro del mundo - Schreckenberg, Stefan; Schmitz, Sabine (Peter Paul Rubens und der Barock im Norden)

Lernwerkstätten - Kottmann, Brigitte (Handbuch Ganztagsbildung)

Clinching in in-situ CT—A numerical study on suitable tool materials - Köhler, Daniel; Kupfer, Robert; Gude, Maik (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Controversial Histories – Current Views on the Crusades. Engaging the Crusades, Volume Three.